"The influence of alaafia on the design and development of Yoruba housing: a case study of Ibadan and Iseyin " (1997)
"This study examines housing developments, both traditional and contemporary, in Yoruba society, within the context of alaafia, the concept of Yoruba well-being. The evaluation ranges in scope from materiality and physical characteristics of a dwelling to the emotional and spiritual satisfaction gained by living there. All of these aspects of a dwelling relate in some way to alaafia. Literature abounds on Yoruba architecture yet the influence of well-being on the design and construction has not been addressed. This study fills that gap. The traditional compound (agbo ile), as the oldest housing type, is researched in greater detail in order to understand basic Yoruba cultural traits and to establish the relationships between a residence and alaafia. Two types of self-contained housing (ile adagbe), and another communal-based type, the ""Brazilian"" (kojusimi-ki-nkojusio), were analyzed with the same parameters used in the evaluation of traditional compounds. This approach allows for a comparative study and exposes any tereotypes held by the Yoruba about particular dwelling types and their residents. The study draws similarities between the various types of housing. It also uncovers some of the changing values within alaafia and Yoruba culture. One's personal living space, its maintenance, ambiance and appearance are subjective issues. Personal preferences guide the prioritization of the traits of alaafia. Although all parts of alaafia may have been satisfied for an individual who lives in an apartment flat, this may not have been accomplished through traditional means. Instead of a shrine (ojubo) in the home, he/she may go to church or the mosque. Instead of being without the wisdom and influence of older generations, a young couple might extend this responsibility towards an older couple also living in the building, or to the landlord. This relationship becomes a pseudo-extended family. The influence of westernization in personal tastes as well as construction materials and methods are also addressed. The use of traditional materials has grown in popularity. This is due to the similarities in performance between modem and traditional materials, and the decreased cost of building with the latter. Recently, sustainability has become an issue in communities and town planning authorities. As a result'there is rising support for building with natural/local materials to avoid half-financed, abandoned projects. The traditional compound (agbo ile) plan is being resurrected in the contemporary courtyard house. Yet, the Brazilian type (kojusimi-kinkojusio) seems to be a closer match to traditional architectural types in terms of alaafia, reflecting the physical and the social worlds of the Yoruba people. Although the physical, economic, cultural and social environment is changing in Yorubaland, the pursuit of alaafia remains constant. The methods and ways that well-being is achieved have changed and impacted the architectural environment. "